Comparison the Angle of Neck Motion Restriction in Using Soft Collars and Rigid Collars - Septiani, Anissa; Anggriani, Atika Febri; Yulianti, Esti Dwi (Gaster, 2026)
Background: Cervical collars are commonly used to provide comfort and restrict cervical motion in post-operative and pain management patients, with an average usage rate of 80.8% in cervical injury cases. Different collar types offer varying degrees of motion restriction, which is critical in patient recovery.  Purpose: This study aims to compare the degree of neck movement restriction between soft cervical collars and rigid cervical collars. Methods: This quantitative research used a cross-sectional study design. A purposive sampling technique was applied to select 20 respondents from a population of 212, based on predefined inclusion and exclusion criteria. Respondents were divided into two intervention groups: 10 participants wore soft collars, and 10 wore rigid collars. Neck movement restriction angles were measured using the Angulus application, focusing on six directions of movement: flexion, extension, right and left lateral flexion, and right and left rotation.  Results: The results showed significant differences in restriction angles between the two collar types. Rigid collars demonstrated greater restriction than soft collars, with mean differences as follows: 29,35(flexion), 15,10 (extension), 17,72 (right lateral flexion), 17,78 (left lateral flexion), 21,93 (right rotation), and 24,02 (left rotation). Conclusion: There is a statistically significant difference in neck movement restriction between soft and rigid collars. Rigid collars are more effective in limiting cervical motion across all measured directions. These findings highlight the importance of selecting the appropriate collar type based on the desired level of immobilization for optimal clinical outcomes.